Adapting to Climate Change in Europe and Central Asia : Background Paper on Water Supply and Sanitation - Evans, Barbara; Webster, Michael (World Bank, Washington, DC, 2017)
In general, the Europe and Central Asia Region (ECA) is predicted to become wetter and warmer as a result of climate change, with more frequent weather extremes (drought, floods, heatwaves, and winter squalls). While in general precipitation in the region is low, around 40 percent is converted to runoff – higher than in any other region. Changes in runoff patterns are likely to be significant across much of the region, with increases in much of the Russian Federation and decreases in most other sub-regions. Overall the outlook for the region is one of increasing uncertainty and extremes in weather events with northern areas becoming wetter and warmer and southern areas drier. This paper is written from the perspective of the utility manager or municipal and government planner. It examines the increasing risk and uncertainty facing utilities in the ECA region and explores some of the potential responses and resources available. It is based on a short literature review which draws on three broad bodies of literature: the first deals with climate change and adaptation in general and provides useful information about likely impacts in the ECA region and generalized policy responses; the second deals with adaptation in water utilities. This literature tends to have little explicit analysis pertaining to the ECA region; and the third examines the performance and operating options of utilities in the ECA region but which tends to have little explicit analysis on the impacts of climate change.